GAME ADDICTION AND ITS EFFECTS ON TEENAGERS’ MENTAL HEALTH - Muhamad Disra Saputra; Marjohan Marjohan; Safrizal Safrizal (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2020)
The aim of this study is to describe the game addiction behavior and its effect on mental health of teenagers. This study used qualitative method. The data collection was carried out in three ways: interview, observation, and documentation. The data were analyzed by using Miles and Huberman’s theories. In order to maintain the validity, the researcher did triangulation techniques. The results of the study showed that online game addiction had an effect on several domains, namely a sense of dependency that was marked by disability to withdraw from the desire to play games. Accordingly, the gamers frequently declared that their life without online gaming was empty. They were intolerance to the use of time, as they said that the time needed to play online games was uncertain, and their disability to control their emotions due to defeat during the games.